Oral Adenoid/Acantholytic Squamous Cell Carcinoma: A Report of two Cases with Review of Literature - Nayak, Shruti D; Jose, M; Sequeira, J (Kathmandu University Medical Journal, 2013)
Adenoid squamous cell carcinoma (ASCC) is an uncommon but well recognized variant of squamous cell carcinoma. It has been reported to originate in the sun exposed skin of the head and neck region. Although rare, there are cases in records which have reported within the oral cavity and nasopharynx. Histologically the lesion shows areas of conventional squamous cell carcinoma along with atypical epithelial cells forming an adenoid pattern. There are insufficient reported cases to establish likely behaviour. Here we report two additional cases of adenoid squamous cell carcinoma, one developing in the floor of mouth and another in the maxillary sinus both were reported in March 2010 in Mangalore, India. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 83-87 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8028